뉴노멀 시대의 공공기관 원격보안 모델 개선방안 - 신승우(SeungWoo Shin); 조인준(In-June Jo) (한국콘텐츠학회 논문지, 22(9), 2022)
The pandemic caused by the COVID-19 virus, which has lasted for the past three years, has changed society and the way people live in many ways. These changes also affect cyberspace, so the pre-pandemic information security model and standards have limitations when applied to the current situation. In this paper, a new method to improve the information security model of public institutions was proposed in consideration of various situations in the new normal era. In other words, through the proposed information security model, the possibility of external intrusion is blocked in advance through the policy and technical supplementation of remote work, which is a weakness of the existing information security operation of public institutions. Also, how to prevent abnormal authentication attempts by building a secure VPN environment, how to prevent social engineering cyber attacks targeting fear and uncertainty caused by COVID-19, and how to use a smooth network and create a remote work environment. For this purpose, methods for securing service availability were additionally presented. 지난 3년간 지속된 COVID-19 바이러스에 의한 팬데믹 사태는 사회와 사람들의 삶의 방식을 다양한 방식으로 변화시켰다. 이러한 변화는 사이버공간에도 영향을 주어 팬데믹 이전의 정보보안 모델과 기준은 현재 상황에 적용할 때 한계가 있다. 본 논문에서는 뉴노멀 시대의 다양한 상황을 고려한 공공기관의 정보보안 모델개선방안을 새롭게 제안하였다. 즉, 제시된 정보보안 모델을 통해 기존의 공공기관 정보보안 운영의 취약점인 원격근무의 정책적, 기술적 보완을 통해 외부 침입의 가능성을 사전 차단한다. 또한 안전한 VPN 환경 구축을 통해 비정상적 인증 시도를 방어하는 방법, COVID-19로 인한 두려움과 불확실성을 노린 사회공학기반 사이버 공격(Social Engineering Cyber Attack)을 예방하는 방법, 원활한 네트워크 사용 및 원격근무 환경 조성을 위해 서비스 가용성을 확보하는 방법 등을 추가로 제시하였다.